Estrategias didácticas en el desarrollo de las macro destrezas en Lengua y Literatura - Naranjo Riera, Lisbeth Katerine (2023)
Education today requires new methodologies for the teaching-learning process, so the teacher must be in constant preparation with the purpose of providing necessary activities that allow the development of skills based on critical thinking. However, the strategies applied by the teacher do not respond to the needs of the students, because rote, repetitive learning and individualism are promoted. To this is added, the difficulties they have in the development of macro skills in Language and Literature.